Ciência com Fronteiras: o francês para fins de mobilidade acadêmica internacional no Instituto Federal do Maranhão - Souza, Vilton Soares de (2019)
This thesis aims to show that it is possible to better prepare the students from IFMA for academic mobility in France, considering the linguistic-enunciative-discursive needs of students who have already experienced the exchange through the Science without Borders program (Ciências Sem Fronteiras) and as a consequence to reflect future offers of French courses for international academic mobility in IFMA. The general objective, therefore, is to present didactic reflections on French teaching and learning for international academic mobility, from a dialogic perspective, based on the experience of IFMA students at French universities. In order to achieve our general objective, the following research question needs to be answered: how can a teaching-learning proposal of French, in the dialogic perspective, respond to the needs of the IFMA exchange students at the French university? To reach this answer, one needs to know: (a) From the point of view of the Brazilian exchange students, what are the main linguistic-enunciative-discursive needs experienced in French universities? and (b) How does a didactic practice focusing on the language as an interaction contribute to the Brazilian programs of international academic mobility? This thesis dialogues with the theoretical and methodological perspective of Bakhtin and the Circle, known as a dialogical perspective, and on the prototypical didactic procedure of French for Academic Purposes (FOU). The context covered is that of professional education in Brazil, based on the Federal Institute of Maranhão – IFMA and the linguistic-enunciative-discursive needs felt by the students in French universities, which must emerge from the analysis of the speeches of the IFMA exchangers by the Science Without Borders program in France. The participants are the professor/researcher and the six students, who experienced the exchange experience in France. The selected corpus covers the period from 2011 to 2017. We applied a questionnaire to the students using the SurveyMonkey platform. The questionnaire along with its answers formed the starting point of the corpus. In addition to the questionnaire, the corpus is composed of an interview (questions and answers) with the purpose of clarifying and/or amplifying the answers of the questionnaire. The results point out obstacles in the integration of the Brazilian students in the French university in three inseparable levels: Linguistic, Enunciative and Discursive. Therefore, the needs are linked to the non-sharing of the French language-culture in use and the non-active understanding of the statements; which leads to the emergence of problems in the construction of knowledge. In order to address this issue, it is necessary to construct didactic practices that enable Brazilian students to become agents of language, intercultural agents, and thus allow them to learn to learn in another way. In the end, the student must be able to exist/act in the academic sphere as a result of an active understanding of the French language